2013
DOI: 10.1038/jcbfm.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia Disrupts Cerebrovascular Reflexes and Worsens Ischemic Perfusion Defect

Abstract: Hyperlipidemia is a highly prevalent risk factor for coronary and cervical atherosclerosis and stroke. However, even in the absence of overt atherosclerosis, hyperlipidemia disrupts endothelial and smooth muscle function. We investigated the impact of hyperlipidemia on resting-brain perfusion, fundamental cerebrovascular reflexes, and dynamic perfusion defect during acute focal ischemia in hyperlipidemic apolipoprotein E knockout mice before the development of flow-limiting atherosclerotic stenoses. Despite el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…Peri-infarct depolarizations typically induced a transient hyperemia in mildly ischemic cortex, and hypoperfusion in more severely ischemic regions ( Figure 3A). Because high-fat diet is known to diminish PID occurrence, 4 we usually detected only 1 PID during the 60-minute imaging period in vehicle controls ( Figure 3B). We, therefore, pooled all ROCK inhibitor treatment groups to gain statistical power for nonparametric testing, and found that ROCK inhibition was associated with fewer PID occurrence.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Peri-infarct depolarizations typically induced a transient hyperemia in mildly ischemic cortex, and hypoperfusion in more severely ischemic regions ( Figure 3A). Because high-fat diet is known to diminish PID occurrence, 4 we usually detected only 1 PID during the 60-minute imaging period in vehicle controls ( Figure 3B). We, therefore, pooled all ROCK inhibitor treatment groups to gain statistical power for nonparametric testing, and found that ROCK inhibition was associated with fewer PID occurrence.…”
Section: Resultsmentioning
confidence: 94%
“…The impact of peri-infarct depolarizations (PIDs) on ischemic perfusion defect was calculated as % change in the area of cortex with residual CBFp30% from immediately before a PID to just after its recovery, as described in detail previously. [12][13][14] In addition, using the preischemic speckle contrast images we determined the t c À 1 values as a measure of resting CBF, as described previously, 4,15 and calculated the resting cerebrovascular resistance (CVR) using the formula CVR (%) ¼ MABP/CBF, where both MABP and CBF were expressed relative to the vehicle group. In a separate cohort of ApoE KO mice treated with vehicle or fasudil for 4 weeks (n ¼ 3 each), we determined the plasma lipid profile (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that hyperlipidemia induces inflammation in the brain [5][6][7] and that hyperlipidemia exacerbates the ischemic brain damage that is linked to neuroinflammation [8,9] . There is also considerable evidence that hyperlipidemia contributes to the disruption of cerebrovascular reflexes and the breakdown of the blood-brain barrier [45,46] . Therefore, the modulation of hyperlipidemia and neuroinflammation via probucol may be an effective therapeutic strategy for reducing the effects of both hyperlipidemia and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, hypercholesterolemia was sufficient to produce vascular dysfunction in animal models including primates. For example, in models where cerebral arteries had minimal or no detectable atherosclerotic lesions, hypercholesterolemia reduced resting CBF, the influence of basally-produce NO on vascular tone, 114116 as well as agonist- and platelet-induced endothelium-dependent relaxation. 117120 Vasoconstrictor responses to endothelin-1 were substantially increased in hyperlipidemic mice.…”
Section: Part I Cerebrovascular Disease: the Prelude To Strokementioning
confidence: 99%